2018
DOI: 10.1038/s41416-018-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant PF-05280014 (a potential trastuzumab biosimilar) versus trastuzumab for operable HER2+ breast cancer

Abstract: PF-05280014 demonstrated non-inferior pharmacokinetics and comparable efficacy, safety and immunogenicity to trastuzumab-EU in patients with operable HER2-positive breast cancer receiving neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 28 publications
6
56
0
13
Order By: Relevance
“…Progression-free survival at 48 weeks was 44.7% and 44.3% for reference and biosimilar trastuzumab, respectively; overall survival was 85.1% and 89.1%, respectively; adverse events affected 94.7% and 98.6% of patients, respectively [40,41]. PF-05280014, another biosimilar of trastuzumab, was reported as having demonstrated equivalence in its primary endpoint in November of the past year; data from this study have not yet been presented [42]. Finally, biosimilar trastuzumab has been investigated only as a single agent, while trastuzumab plus pertuzumab is considered the standard of care.…”
Section: Biopharmaceuticals In Breast Cancermentioning
confidence: 99%
“…Progression-free survival at 48 weeks was 44.7% and 44.3% for reference and biosimilar trastuzumab, respectively; overall survival was 85.1% and 89.1%, respectively; adverse events affected 94.7% and 98.6% of patients, respectively [40,41]. PF-05280014, another biosimilar of trastuzumab, was reported as having demonstrated equivalence in its primary endpoint in November of the past year; data from this study have not yet been presented [42]. Finally, biosimilar trastuzumab has been investigated only as a single agent, while trastuzumab plus pertuzumab is considered the standard of care.…”
Section: Biopharmaceuticals In Breast Cancermentioning
confidence: 99%
“…CPT-6 was previously assessed in studies using both settings, but this was due to small changes in the production process that required duplication of all the comparability exercises . 4 For PF-05280014, clinical equivalence was based on a study in the metastatic setting, which was reported at ESMO by Pegram et al 1 Lammers et al report on a second trial, 8 innovatively added into the development, which has also assessed PF-05280014 in the neoadjuvant setting. Paired with their earlier findings, this second trial may appear as the icing on the cake.…”
Section: Mainmentioning
confidence: 99%
“…8 The 47% and 50% pCR rates achieved by PF-05280014 and Herceptin, respectively, provide a stratified difference for pCR of -2.81% (95% CI -16.58%/10.96%) based on investigator assessment. These differences and the 95% CI values are in line with the reported values provided by other biosimilar competitors in the same setting (Table 1).…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…CT-P6 (HerzumaÂź, Celltrion Healthcare, Incheon, ROK/Teva Pharmaceuticals, Petach Tikwa, Israel) and PF-05280014 (TrazimeraÂź, Pfizer, New York, NY, USA/Hospira, Lake Forest, IL, USA) were evaluated in both mBC and eBC [14,15,16,17], ABP 980 (KanjintiÂź, Amgen, Thousand Oaks, CA, USA) [18] and SB3 (OntruzantÂź, Samsung Bioepis, Incheon, ROK/Daewoong Pharmaceuticals, Seoul, ROK/Merck (MSD), Kenilworth, NJ, USA) [19,20] only in eBC, and MYL-1410 (OgivriÂź, Biocon, Bangalore, India/ Mylan, Canonsburg, PA, USA) [21] and BCD-022 (HERtiCADÂź, Biocad, Saint Petersburg, Russia) only in mBC (NCT01764022). All biosimilars were evaluated with the recommended equivalence trial design, except for BCD-022 which was evaluated in a non-inferiority trial.…”
Section: Clinical Trials For Biosimilar Trastuzumabmentioning
confidence: 99%